Regime for Bowel Preparation in Patients Scheduled to Colonoscopy: Low-Residue Diet or Clear Liquid Diet? Evidence From Systematic Review With Power Analysis. Issue 1 (January 2016) - Song, Guo-Min; Tian, Xu; Ma, Li; Yi, Li-Juan; Shuai, Ting; Zeng, Zi; Zeng, Xian-Tao
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Clear liquid diet (CLD) is used to perform bowel preparation before colonoscopy traditionally, but several clinical studies indicated that low-residue diet (LRD) generates equal effects to CLD and a conclusive conclusion has not yet been yielded. The systematic review was performed to address this conflict and facilitate informed decision-making eventually. To capture randomized controlled trials (RCTs) comparing LRD with CLD in terms of bowel preparation, a search was performed in PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Science Direct, recent conference abstracts, Google Scholar, and Clinicaltrials.gov through May 2015. We performed all meta-analyses based on fixed- or random-effects model, which is generated from clinical characteristics and methodology. Moreover, the G ∗ Power software was adopted to achieve statistical power for each outcome. In total, we captured 109 potential citations at initial search stage and 2 topic-related articles were included through other sources. After critical appraisal, 7 RCTs were eligible for our inclusion criteria. Meta-analyses generated similar effects in bowel preparation quality, efficacy of colon cleansing, and compliance with recommended dietary regime when LRD versus CLD regime, but patients who were prescribed to receive LRD have slightly better tolerance (RR, 1.06; 95% CI, 1.02–1.11) and tended to repeat the same preparation regime in future (RR, 1.17; 95% CI, 1.09–1.26) relative to patients in CLD. Importantly, both regimes resulted in similar adverse events (AEs). With the best available evidence, LRD could be recommended to be as standard regime for bowel preparation prior to colonoscopy.